Memahami Penerapan Manajemen Pengembangan Masyarakat a la Rasulullah - Yanti, Fitra (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The success of Islamic Community Development during the time of the Prophet Muhammad is the basis for implementing Islamic Community Development programs today. This article discusses the success of community development management carried out during the time of the Prophet Muhammad period. The aim of this research is to see in detail the applications and areas that demonstrated the success of the management of the Prophet's time. The method used is content analysis of texts related to the implementation of PMI Management during the time of the Prophet. Content analysis conducted based on literature that explains how the Prophet Saw implemented community development management. It is conducted from planning, organizing, actualizing and evaluating efforts to build and develop community welfare in his time. The results obtained show that the Prophet Muhammad exemplified the principles of community empowerment management in every da'wah activity by delegating jobs to appropriate and competent people in their respective fields, such as religious, social, economic, political and military, conflict management, as well as maintain environmental sustainability principles. The implication is that the results of this analysis confirm the exemplary management of Islamic community development that originates directly from the treatise handed down by Muhammad the Prophet.Keywords: Revelation, Management of the Prophet, Empowerment Theory, Development of Muslim Society, ABSTRAKKesuksesan Pengembangan Masyarakat Islam pada masa Nabi Muhammad merupakan dasar dari pelaksanaan program-program Pengembangan Masyarakat Islam hari ini. Artikel ini mendiskusikan kesuksesan manajemen pengembangaan masyarakat yang dilakukan pada masa Rasulullah Saw. Tujuannya untuk merinci penerapan dan bidang yang menunjukkan keberhasilan manajemen masa Rasulullah Saw. Metode yang digunakan adalah content analysis terhadap teks yang berkaitan dengan pelaksanaan Manajemen PMI pada masa Nabi. Analisis isi dilakukan terhadap literatur yang menjelaskan bagaimana Nabi saw. mengimplementasikan manajemen pengembangan masyarakat mulai merencanakan, mengorganisasi, mengaktualisasi, dan mengevaluasi upaya membangun dan mengembangkan kesejahteraan masyarakat di masanya. Hasil yang didapatkan bahwa Nabi Muhammad mencontohkan prinsip-prinsip manajemen pemberdayaan masyarakat dalam setiap kegiatan dakwah dengan melimpahkan tugas kepada orang yang tepat dan kompeten di bidang masing-masing, seperti bidang keagamaan, sosial kemasyarakatan, perekonomian, politik dan militer, pengelolaan konflik, serta prinsip menjaga kelestarian lingkungan hidup. Implikasinya bahwa hasil analisis ini menjadi penegasan terhadap teladan manajemen pengembangan masyarakat Islam bersumber langsung kepada risalah yang diwariskan Rasulullah Saw.Kata Kunci: Pewahyuan, Manajemen Rasulullah, Teori Pemberdayaan, Pengembangan Masyarakat Muslim,